2010
DOI: 10.1111/j.1460-9568.2010.07217.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic links between theta executive functions and alpha storage buffers in auditory and visual working memory

Abstract: Working memory (WM) tasks require not only distinct functions such as a storage buffer and central executive functions, but also coordination among these functions. Neuroimaging studies have revealed the contributions of different brain regions to different functional roles in WM tasks; however, little is known about the neural mechanism governing their coordination. Electroencephalographic (EEG) rhythms, especially theta and alpha, are known to appear over distributed brain regions during WM tasks, but the rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
126
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(157 citation statements)
references
References 42 publications
25
126
1
5
Order By: Relevance
“…In our recent study using single visual and auditory WM tasks, the frontal theta activity was mainly observed during the manipulation period and not the maintenance periods, whereas posterior alpha activity was enhanced both in the manipulation and maintenance periods (Kawasaki et al, 2010). Building upon those previous findings, the present study demonstrated that frontal theta activity further increased in the dual WM task in comparison to the single VWM task, whereas parietal alpha activity did not differ between the single and dual WM tasks.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…In our recent study using single visual and auditory WM tasks, the frontal theta activity was mainly observed during the manipulation period and not the maintenance periods, whereas posterior alpha activity was enhanced both in the manipulation and maintenance periods (Kawasaki et al, 2010). Building upon those previous findings, the present study demonstrated that frontal theta activity further increased in the dual WM task in comparison to the single VWM task, whereas parietal alpha activity did not differ between the single and dual WM tasks.…”
Section: Discussionsupporting
confidence: 54%
“…In addition to confirming previous reports that these oscillations are involved in VWM (; Klimesch et al, 2008;Jensen & Tesch, 2002;Jensen et al, 2002), the present study was able to dissociate their functions. Frontal theta activities have been associated with central executive functions including mental manipulation and calculation tasks (Kawasaki et al, 2010) and in supporting VWM storage during high-VWM loads and demands (Curtis & D'Esposito, 2003;Kawasaki & Watanabe, 2007;Sakai et al, 2002). Parietal alpha activity has been proposed to reflect simple WM storage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[52][53][54] The theta rhythm (4 to 8 Hz) has been observed during a number of cognitive processes, and its most prominent form, fronto-medial theta, is believed to originate from limbic and associated structures in the medial prefrontal cortex. [55][56][57][58] These theta oscillations subserve central executive function, integrating affective and cognitive sources of information, as necessary in working memory tasks [59,60] as well as in action monitoring. [58] Concerning affect, early reports mention an increasing 'hedonic' theta activity after interruption of pleasurable stimulation, but studies in children between 6 months and 6 years of age showed increases in theta activity upon exposure to pleasurable stimuli.…”
Section: Frequency-domain Correlatesmentioning
confidence: 99%